THE LEGAL ARRANGEMENT OF WAGE PROTECTION BASED ON THE PRINCIPLE OF LEGAL CERTAINTY - Y Yetniwati (Jurnal Dinamika Hukum, 2016)
The wage protection in Indonesian positive law is still not provide legal certainty for the weaker party in the aspect of social economic. In every anniversary of May Day, labor union always demanded to abolish the wage cost, which the Government Regulation No. 78 Year 2015 leanihg to the interests of investors. The principle of legal certainty in the norm of wage protection needs to be realized with respect to: the concept of wage protection, lack of certainty purpose of law, established by the competent authorities, accepted by society, legal materials in accordance with the legal hierarchy, the company's obligation to make books wages, and avoid multiple interpretations in legal norms.Keywords:  protection of wages, labor, legal certainty.